Orchids of the Occupied Palestinian Territories (West Bank, Palestine) - Pahl, Julius; Qumsiyeh, Mazin B. (Mediterranean Botany, 2021)
Literature data and new records of members of the orchid family (Orchidaceae) in the Occupied Palestinian Territories were reviewed and updated with field data. Using data from the Palestine Museum of Natural History (PMNH), data from fellow botanists, and the Biodiversity databases (BioGIS and GBIF), the distribution patterns were analyzed with the QGIS package. Twenty-three taxa of eight genera were found in this preliminary study. For two species, no recent data from the last 20 years were available and in some cases likely declined due to human activity. Most species are from the Mediterranean phytogeographical zone, Epipactis veratrifolia Boiss. & Hohen was found in the Sudanian-Ethiopian zone (Dead Sea valley). The majority of the species found prefer semi-open shrublands (garrigue). Nine species had fewer than 20 records overall. Trends observed from the historical data, and current spatial data revealed major threats, including habitat fragmentation, urbanization, intensification of agricultural land use, afforestation and reduced precipitation due to global warming. We noted the proximity to thorny shrubs in many species indicating pressure by grazing animals during field visits. As recent data is scarce, surveys of sites where rare species have been encountered in the past are recommended, and measures to protect vulnerable populations are discussed.